1971
DOI: 10.1126/science.173.3999.839
|View full text |Cite
|
Sign up to set email alerts
|

Pineal N -Acetyltransferase Activity: Effect of Sympathetic Stimulation

Abstract: Stimulation of preganglionic sympathetic fibers to the superior cervical ganglia elevates the activity of pineal N-acetyltransferase. After the stimulation-induced rise in enzyme activity, a return toward baseline levels occurs whether or not nerve stimulation is continued. The ability of pineal N-acetyltransferase activity to fall in the presence of stimulation may account for the persistence of its rhythm in blinded animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

1972
1972
1990
1990

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…1661 cervical ganglion elevates pineal N-acetyltransferase activity (14). The nocturnal increase in N-acetyltransferase activity is abolished by exposure of the animals to light, denervation by superior cervical ganglionectomy (9,15), decentralization, or by treatment with reserpine, propranolol, or cycloheximide (9).…”
mentioning
confidence: 99%
“…1661 cervical ganglion elevates pineal N-acetyltransferase activity (14). The nocturnal increase in N-acetyltransferase activity is abolished by exposure of the animals to light, denervation by superior cervical ganglionectomy (9,15), decentralization, or by treatment with reserpine, propranolol, or cycloheximide (9).…”
mentioning
confidence: 99%
“…Recent studies have shown that 3-(3,4-dihydroxyphenyl)-L-alanine (L-DOPA), catecholamines, or monoamine oxidase inhibitors induce N-acetyltransferase activity in rat pineal organ in vivo that is blocked by prior treatment with a j8-adrenergic blocking agent (8). Electrical stimulation of the sympathetic nerve that innervates the rat pineal organ also causes an increase in N-acetyltransferase activity (9). These observations suggest that the neurotransmitter released from sym-2547 pathetic nerves regulates the activity of N-acetyltransferase in the pineal organ by stimulating the adrenergic ,-receptor and adenosine 3': 5'-cyclic monophosphate (cyclic AMP), and that the release of norepinephrine is modulated by environmental light and darkness.…”
mentioning
confidence: 99%
“…The nocturnal rise was completely blocked by ganglionectomy or by decentralization of the superior cervical ganglion (3). Electrical stimulation of the sympathetic nerve that innervates the pineal organ resulted in a more than 3-fold elevation of N-acetyltransferase activity (4). N-Acetyltransferase activity increased in response to norepinephrine or dibutyryl adenosine 3': 5'-cyclic monophosphate in cultured rat pineal organ (5).…”
mentioning
confidence: 99%